TRANSFORMATION OF ORGANIZATIONAL COMMUNICATION IN THE DIGITAL ERA: A LITERATURE STUDY ON STRATEGIES, CHALLENGES, AND THEIR IMPACT ON ORGANIZATIONAL EFFECTIVENESS - Rahel Farhanah Azzahra; Nurul Indah Saraswati; Nensy Anggreini Br Ginting; Tampan Hawari Amru; Feni Khairifa (OPINI: Journal of Communication and Social Science, 2025)
This study examines the transformation of organizational communication in the digital era through a Systematic Literature Review (SLR) approach. The research aims to identify key strategies, challenges, and impacts of digital communication on organizational effectiveness. Drawing on peer-reviewed journal articles indexed in Google Scholar, SINTA, DOAJ, and other academic databases, the study synthesizes recent literature addressing digitalization, information technology implementation, leadership communication, and employee engagement. The findings indicate that digital communication significantly enhances operational efficiency, accelerates information flow, supports cross-functional collaboration, and enables data-driven decision-making. However, the transformation process also presents critical challenges, including digital skill gaps, resistance to change, information overload, cybersecurity risks, and ethical concerns. Leadership communication emerges as a central factor in managing digital change, particularly in fostering trust, psychological safety, and organizational resilience. Overall, the study concludes that digital communication transformation positively influences organizational effectiveness when supported by adaptive culture, strengthened digital literacy, ethical governance, and balanced integration between digital and face-to-face communication.